Visualizing recycling synaptic vesicles in hippocampal neurons by FM 1-43 photoconversion - Harata, Nobutoshi (The National Academy of Sciences, 2001)
Exo–endocytotic turnover of synaptic vesicles (SVs) at synapses between hippocampal neurons in culture was examined by electron microscopy (EM). We carried out photoconversion (PC) of the fluorescent endocytotic marker FM 1-43 by using 3,3′-diaminobenzidine to convert the dye signal into an electron-dense product. Electron-dense products were located almost exclusively in SVs, whose densities were bimodally distributed in two sharply demarcated populations, PC-positive (PC+) and PC-negative (PC−). The median densities of these populations did not vary with the proportion of vesicles stained within a presynaptic terminal (bouton). The proportion of PC+ SVs remained constant across consecutive thin sections of single boutons, but varied greatly from one bouton to another, indicating marked heterogeneity in exo-endocytotic activity. Our experiments indicated that only a minority of SVs were stained in most boutons after stimuli known to cause complete turnover of the functional vesicular pool. A direct spatial correlation was found between FM 1-43 fluorescent spots seen with light microscopy and PC+ boutons by EM. The correlation was clearer in isolated boutons than in clusters of boutons. Photoconversion in combination with FM dyes allows clarification of important aspects of vesicular traffic in central nervous system nerve terminals.